THE INFLUENCE OF GIVING A POCKET BOOKLET ABOUT CERVICAL CA ON MOTHER'S INTEREST IN CONDUCTING IVA EXAMINATIONS IN THE WORKING AREA OF PUDAK HEALTH CENTER PONOROGO REGENCY - Fifit Endang Sulistyaningsih (Journal for Research in Public Health, 2022)
Cervical cancer is a disease that is categorized as a malignant disease of the cervix or uterine cervix. The aim of this research is to determine the effect of providing a pocket book about cervical ca on mothers' interest in carrying out VIA examinations in the Pudak Health Center work area, Ponorogo Regency. This research uses a quantitative analytical research design Pra Eksperimen One Group pre test post test Design. The population in this study were mothers aged 35-55 years at the Pudak Health Center, Ponorogo Regency, a total of 1539 respondents. The sample in this study was some mothers aged 35-55 years at the Pudak Health Center, Ponorogo Regency who came to counseling using the technique Accidental Sampling. Data were collected using questionnaires and the Ca Cerviks pocket book. Data analysis to see the relationship between the independent variable and the dependent variable uses statistical tests Wilcoxon with a significant level of ρ < 0.05. The research results showed that almost all of the respondents were not interested in carrying out an IVA examination before being given education using a pocket book, as many as 87 respondents (87%) were not interested in carrying out an IVA examination. Almost all respondents (82%) were interested in carrying out an IVA examination after being given education using a pocket book. Results Data analysis using statistical tests Wilcoxon The significant value obtained was ρ < 0.05 (0.000 <0.05), meaning that there was an influence of giving a pocket book on the mother's interest in carrying out an IVA examination at the Pudak Health Center, Ponorogo Regency. Limitations in this research are the small number of respondents, media, and respondents' time so the research is not perfect.